Is the Tourism Industry A Fragile Heavy Weight? Validation through a Literature Review of Tourism System Shocks - Zhou Zibanai (Aim&Scope. Ottoman, 2023)
The global tourism industry has arguably become the world`s pre-eminent sector, contributing about $3.6 trillion to the global gross domestic product (GDP) and employing 225 milion people (World Travel and Tourism Council, 1997). Despite its acknowledged economic power and apparent resiliency, tourism is highly vulnerable to internal and external shocks ranging from political conflicts, natural disasters to epidemic diseases. This article argues that the tourism industry is increasingly becoming susceptible to crisis events to the extent that tourism players have to contend with this reality in their daily operations. The study employed literature narratives as data sources from primed tourist destinations that have been hit by tourism crises. This study has some significance of confirming that tourists evaluate destinations according to safety and risk factors. The study further revealed that tourism crises do not only impair a tourist destination`s image but also weaken and destroy the competitive advantage of the destination. The review identified the quartet of terrorism, epidemic diseases, tsunamis and political conflicts as having the most devastating effects on the global tourism industry. Recommendations include less reliance upon tourism as an economic sector in favour of economic diversification, identification of potential destination specific crises and putting in place pro-active crisis management and recovery strategies. Future studies should explore how positive tourism shocks impact on the global tourism industry.